Effectof mycorrhiza applications on nutrient uptake in Prunus rootstock under water stress conditions (Current Horticulture, 2024)
The experiment was conducted in a glass green house using pots to compare grafted and ungrafted plants. Four different  rootstocks, namely Rootpac 40, Rootpac R, GF 677, and Garnem, were utilized. The control plants (K100) were irrigated to  maintain a water level equivalent to 100% of the field capacity. For the K55 application, water was provided at 55% of the K100  irrigation level, while the K40 application received water at 40% of the K100 application. During the 2020 trial, water availability  was limited, resulting in restricted water application to the plants. Half of the seedlings were grafted with the Carolina nectarine  variety. In the 2021 trial, limited water application was implemented by inoculating both the grafted and non-grafted nectarine  plants with Glomus mosseae mycorrhiza species. Under drought stress, the mycorrhizae-inoculated seedlings exhibited positive  effects on the concentrations of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg) in their leaves.
Keywords: Stone fruits rootstocks; Drought resistance/tolerance; Mycorrhiza; Plant nutrients; Macro elements